Synthesis of Heterodiarylmethanes via Metallaphotoredox Decarboxylative Arylation - Yanez, Amanda; Jeanneret, Alexandria D. M. (Synlett, 2024)
A metallaphotoredox-catalyzed synthesis of heterodiarylmethanes using mild reaction conditions, commercially available substrates, and bench-stable catalysts is demonstrated. Moderate yields are obtained, and further derivatization of the newly formed benzylic position is shown.
Keywords: metallaphotoredox; decarboxylative arylation; heterodiarylmethanes; photochemistry